Social cost-benefit analysis of tobacco control policies in the Netherlands. (13th November 2019) - de Kinderen, R J A; Wijnen, B F M; Evers, S M A A; Hiligsmann, M; Paulus, A T G; de Wit, G A; van Gils, P F; Over, E A B; Suijkerbuijk, A W M; Smit, F
Abstract: Background: In the Netherlands approximately 23% of the population of 15 years and older smokes. The main research questions were to identify what social costs- and benefits can be expected when various tobacco control policies would be implemented in The Netherlands, how do costs and benefits change over time, and which sectors in society could expect to incur costs and in which sectors accrue profits. Methods: A SCBA was conducted using a combination of the Chronic Disease Model developed by the National Institute for Public Health and the Environment (RIVM), the SimSmoke model and a specially designed excel model. Policies included both tax increases (i.e. increase of excise tax on tobacco of 5% or 10% each year) and a policy package as proposed by the World Health Organization (i.e. including mass media campaigns and mediabans). Results: When no new policy measures are implemented, the prevalence of smoking will decrease by 2.3 percentage points over the next 35 years. The policies reviewed in this report have the potential to decrease smoking prevalence by 14.2 percentage points (and in a 'smoking-free society scenario, by as much as 17.4 percentage points). Furthermore, the results show that the intervention costs for all scenarios are minimal, and that investing in health is beneficial as seen from both the public health and fiscal perspective. Conclusions: This study demonstrated that reducing the prevalence of smoking has beneficial effects for various stakeholders within the Dutch society: such as employers (e.g. increased productivity) and consumers (e.g. increase quality of life).